Research on Windows memory protection mechanism - Ting-ting LU; Jun-feng WANG (网络与信息安全学报)
Over the past three decades,attacks exploiting Windows memory holes have emerged in an endless stream,and the usual means is to attack control-data to hijack the execution flow of the program.To this end,Microsoft has added layers of protection mechanisms to Windows to prevent such attacks.But at this stage,the defensive mechanisms deployed on Windows cannot prevent attacks against non-control-data.In view of the published articles lacking comprehensive study of Windows memory protection mechanism,a detailed introduction to Windows memory protection mechanism and its breakthrough techniques,and non-control-data protection research status was conducted.On this basis,the challenges of Windows memory protection were analyzed and the future of memory protection was discussed.